Patient Perception of the Remote Versus Clinic Visits for Interrogation of Implantable Cardioverter Defibrillators. Issue 1 (March 2020) - Srivatsa, Uma N.; Joy, Kelly C.; Zhang, Xin J.; Fan, Dali; Oesterle, Adam; Birgersdotter-Green, Ulrika
Abstract : Implantable Cardioverter Defibrillators (ICDs) are used in the management of sudden cardiac arrest. Compared with clinic visits, remote interrogation of these devices has shown clinical benefit and lower cost. We hypothesize that demographic and socioeconomic factors influence patient satisfaction with remote monitoring and therefore the choice of a pathway for follow-up. Questionnaires were mailed to 85 patients (mean age 63 ± 13.5 years, 73% male), with ICDs implanted for primary prevention of sudden cardiac arrest. Information regarding education, social support, employment, and income was collected. To compare clinic and remote monitoring, patients were given questionnaires to assess which parameters they consider important: convenience, accuracy, human contact, scheduling, and cost. Of the 34 responders, patients rated clinic visit to be as accurate with better opportunity to ask questions and better human contact, but there was no difference in perception of convenience, scheduling, or cost between the 2 groups. Significant number of patients dropped from the labor market after ICD implantation; however labor status, education, or income did not influence the preference of clinic appointment. Survey respondents preferred clinic to remote interrogation because they believe clinic appointments allow better interaction. Educating patients about the benefits of remote interrogation and improved communication will enhance utilization of this sophisticated technology for superior patient care.